2011
DOI: 10.1590/s0100-83582011000500015
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidade de herbicidas utilizados na cultura da cana-de-açúcar à bactéria diazotrófica Azospirillum brasilense

Abstract: RESUMO -Objetivou-se neste trabalho identificar herbicidas utilizados na cultura da canade-açúcar que não alteram o crescimento ou a capacidade de fixação biológica de nitrogênio (FBN) Palavras-chave: Saccharum spp., fixação biológica de nitrogênio, pesticidas.ABSTRACT -The objective of this work was to identify the herbicides applied on sugarcane that do not affect the growth nor the process of biological nitrogen fixation (BNF) of the diazotrophic bacterium Azospirillum brasilense. Commercial doses of eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…To Pacheco & Cantalice (2011), this can occur by soil compaction and consequent difficulty of root development, while Bassinelo et al (1984) reported that this situation may be associated with phytosanitary issues. Procópio et al (2011) correlated it with weed-crop competition, and Salvi et al (2007), with the fact that ratoons are uprooted during mechanical harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…To Pacheco & Cantalice (2011), this can occur by soil compaction and consequent difficulty of root development, while Bassinelo et al (1984) reported that this situation may be associated with phytosanitary issues. Procópio et al (2011) correlated it with weed-crop competition, and Salvi et al (2007), with the fact that ratoons are uprooted during mechanical harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…O método mais eficiente de controle das plantas daninhas tem sido o químico, isso devido principalmente ao rendimento operacional e ao custo por área quando comparado com os demais métodos (Procópio, 2011). Aliado a isso, o maior conhecimento da flora de planta daninha nas áreas de produção pode contribuir para a redução nos custos de controle (Kuva et al, 2007;2008).…”
Section: Introductionunclassified
“…Vários estudos mostram que os pesticidas podem apresentar toxicidade também a organismos não-alvos. Como exemplo, são comprovados casos de herbicidas sendo tóxicos a bactérias (Santos et al, 2006;Procópio et al, 2011), a fungos (Andaló et al, 2004) e a insetos (Giolo et al, 2005;Stefanello Júnior et al, 2011). Neste sentido, é importante, para o sucesso da tecnologia de inoculação de bactérias diazotróficas, que os pesticidas utilizados na cana-de-açúcar não apresentem efeitos bactericidas, bacteriostáticos ou mesmo prejudiquem a eficiência da fixação biológica do nitrogênio (FBN) desses micro-organismos.…”
Section: Introductionunclassified